Performance analysis of Arithmetic Mean method in determining peak junction temperature of semiconductor device - Muthuvalu, M.S. (Ain Shams University, 2015)
High reliability users of microelectronic devices have been derating junction temperature and other critical stress parameters to improve device reliability and extend operating life. The reliability of a semiconductor is determined by junction temperature. This paper gives a useful analysis on mathematical approach which can be implemented to predict temperature of a silicon die. The problem could be modeled as heat conduction equation. In this study, numerical approach based on implicit scheme and Arithmetic Mean (AM) iterative method will be applied to solve the governing heat conduction equation. Numerical results are also included in order to assert the effectiveness of the proposed technique. Â© 2015 Faculty of Engineering, Ain Shams University.